Pembinaan dan Pengawasan Pemerintahan di Daerah Surabaya - Manurung, Grace Jean; Aswad, Jurniyati; Suharmin, Keith Xsandrawitz; Indah, Dini Permata; Darmawan, Ivan (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Government development and supervision in the Surabaya area is an important aspect in ensuring good and effective governance. This research aims to analyze the mechanisms, challenges and impacts of guidance and supervision carried out by the central government on regional government in Surabaya. Through qualitative methods, data was collected through in-depth interviews with government officials and study of related documents. The research results show that effective guidance and supervision can improve accountability, transparency and regional government performance. However, there are also several obstacles such as lack of resources and coordination that need to be overcome to achieve optimal results